Tuberculous peritonitis in patients on peritoneal dialysis: a 35-year experience from a large medical center in Northern Taiwan. Issue 1 (31st December 2023) - Yang, Tzu-Yi; Tian, Ya-Chung; Yen, Tzung-Hai; Chang, Ming-Yang; Lin, Chan-Yu; Liu, Shou-Hsuan
Abstract: Introduction: Tuberculous peritonitis (TBP) is a rare but fatal complication in patients on peritoneal dialysis (PD). In this study, we aimed to determine the demographic features, clinical features, laboratory parameters, and clinical outcomes of PD patients with TBP and to clarify possible risk factors for mortality. Materials and methods: We retrospectively reviewed 2084 PD patients from January 1985 to December 2019. The diagnosis of TBP was established by positive peritoneal fluid culture for Mycobacterium tuberculosis . Results: 18 patients were diagnosed with TBP. The incidence was 2.029 episodes per 1000 patient-years. The most common symptom was fever (94.4%), followed by cloudy effluent (83.3%) and abdominal pain (83.3%). The average peritoneal dialysis effluent (PDE) white blood cell (WBC) count was 172.7 cells/μL. Nine patients (50%) had WBC counts lower than 100 cells/μL and 13 patients (72.2%) had neutrophilic predominant WBC counts. Acid fast stain (AFS) was positive in 7 patients (38.9%). Only 2 patients (11.1%) continued with PD after TB infection, while 10 patients (55.6%) changed to hemodialysis. Seven patients (38.9%) died within 1 year. Significant differences were observed in sex ( p = 0.040), the presence of diabetes mellitus ( p = 0.024), and PD catheter removal ( p < 0.001) between TBP patients with and without mortality. However, none of them was a significant factor for 1-year mortality in multivariate Cox regression model. Conclusion: Physicians should pay attention to the unusual presentations of peritonitis, especially if symptoms include fever or an initial low PDE WBC count. Catheter removal is not mandatory if early diagnosis and appropriate therapy are available.